Bioinoculant production composed by Pseudomonas sp., Serratia sp., and Kosakonia sp., preliminary effect on Allium cepa L., growth at plot scale (Universitas Scientiarum, 2021)
Phosphorus (P) is an essential nutrient for plant’s development, and its deficiency restricts crop yield. To meet P requirements in agricultural settings, a low-cost culture medium (MT11B) was designed in which a bioinoculant was produced consisting of three bacterial isolates capable of solubilizing P from phosphoric rock (PR). Pseudomonas sp., Serratia sp., and Kosakonia sp. exhibited P solubilization in SMRS1 agar modified with PR (5.0 g L-1), as source of inorganic P. Sowings by isolation were made of the three bacteria on DNAse- and Blood-agar to rule out pathogenicity. At the interaction tests, no inhibition halos were observed; demonstrating there was no antagonism among them, thus they were used to constitute a consortium. Growth curve (12 h) in MT11B demonstrated consortium grew in presence of PR, brewer’s yeast hydrolysate, and glucose at concentrations (2.5 g L-1) fourfold lower than those in SMRS1 (10.0 g L-1); obtaining phosphate solubilizing bacteria of (10.60 ± 0.08/ log10 CFUmL-1 and, at 6 h of culture, acid and alkaline phosphatase enzyme volumetric activities of 2.3 ± 0.8 and (3.80 ± 0.13) UP, respectively. The consortium, releasing phosphorus at a rate of (45.80 ± 5.17) mg L-1 at 6 h of production, was evaluated as bioinoculant in onion plots for five months. Plants receiving a treatment that included 500 mL (10 x 107 CFU mL-1) of bioinoculant plus 100 kg ha-1 of an organic mineral fertilizer exhibited the highest determined response variables (170.1 ± 22.2) mm bulb height, (49.4 ± 6.5) mm bulb diameter, (9.0 ± 1.8) g bulb dry weight, and 15.21 mg bulb-1 total phosphorus (p < 0.05).